Skin Microbiota Was Altered in Crocodile Lizards (Shinisaurus crocodilurus) With Skin Ulcer - Jiang, Haiying; Luo, Shuyi; Zhou, Jiabin; Huang, Wenzhong; Li, Linmiao; Zhang, Xiujuan; He, Jiasong; Chen, Jinping (Frontiers in Veterinary Science, 2022)
Skin diseases commonly affect reptiles, but their relationships to the closely related skin microbiome are not well understood. In recent years, both the wild and captive populations of the crocodile lizard, a Class I protected endangered animal in China, have suffered serious skin diseases that hamper the rescue and release projects for their conservation. This study conducted a detailed prevalence investigation of a major dermatosis characterized by foot skin ulcer in crocodile lizards. It should be noticed that skin ulcer has been prevalent in both captive and wild populations. There was positive correlation between skin ulcer and temperature, while no significant relationship between skin ulcer and humidity, sex, and age. We further studied the relationship between skin ulcer and the skin microbiota using metataxonomics. Results showed that the skin microbiota of crocodile lizards was significantly different from those of the environmental microbial communities, and that skin microbiota had a significant relationship with skin ulcer despite the impact of environment. Both bacterial and fungal communities on the ulcerated skin were significantly changed, which was characterized by lower community diversity and different dominant microbes. Our findings provide an insight into the relationship between skin microbiota and skin disease in reptile, serving as a reference for dermatological etiology in wildlife conservation.